Border contagion: transit migration from the Mediterranean to the Atlantic c. 1860-1914 - Liberatore, R (2019)
My thesis looks at transit migration from the Mediterranean to the Atlantic in the late nineteenth and early twentieth centuries. I follow the development of both the legal and illegal trade in order to account for the persistence of clandestine flows despite the liberalisation of emigration, with the removal of bans on exit in emigration countries and the transition to the bureaucratic regulation of migration flows. This includes examining not only the causes behind clandestine migration, but also the ways in which clandestinity was legislated for, policed, classified and ultimately archived. Documentary checks on identity are thus considered alongside migration laws, the policing of emigration agents, the regulation of the hospitality industry in ports of transits, controls at embarkation and sanitary policy. Its chronology extends from the beginning of mass transatlantic migration from the Mediterranean, starting in the 1870s and 1880s, until the outbreak of World War One, which saw a sudden decrease in migration from Europe (including the Mediterranean) to the Americas and the hardening of migration controls in both countries of origin and arrival for the purpose of conscription and defence. This time arc was punctuated by various crises in migration control, resulting from a number of factors, such as disease epidemics or the feverish spread of propaganda. Although the thesis takes a comparative and interactionist approach to Mediterranean transit flows, ranging from the Ottoman empire and Greece in the east to the Levant in the south and Italy in the west, it focuses primarily on the ‘western transit corridor’ that linked the port cities of Beirut, Naples and Marseilles.